Analisis Penyebab Downtime Pada Mesin Produksi Pupuk NPK Granul Compaction Menggunakan Metode Root Cause Analysis di PT XYZ - Hidayatullah, Fajar Rizky; Joumil Aidil SZS (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The fertilizer industry plays a strategic role in supporting agricultural productivity and national food security. However, production effectiveness is often constrained by machine downtime, which negatively affects operational performance. This study aims to analyze the main causes of machine downtime in the NPK granular compaction production process at PT XYZ and to propose appropriate improvement strategies. The research method employs downtime analysis using a Pareto diagram to identify the machine contributing the highest downtime, followed by root cause analysis using a Fishbone (Ishikawa) diagram and the 5W+1H method. The Pareto analysis results indicate that the Compact machine was the largest contributor to downtime during the October 2025 period, with a total duration of 395.23 hours. Fishbone analysis reveals that downtime is influenced by multiple interrelated factors, including machine, method, manpower, material, measurement, and working environment. Furthermore, the 5W+1H analysis shows that failures of key components such as the roller press, crusher chain, bearings, screen, and Teflon were caused by high workload, inadequate maintenance practices, non-compliance with standard operating procedures, substandard spare part quality, incomplete downtime records, and unfavorable working conditions. Based on the findings, strengthening the implementation of preventive maintenance is recommended as the primary strategy to reduce downtime, improve machine productivity, and enhance the overall efficiency of the NPK granular compaction production process.